PENENTUAN CALON PASANGAN PERKAWINAN BERDASARKAN WETON DI KECAMATAN KANDEMAN KABUPATEN BATANG PERSPEKTIF DALIL ‘URF - Rosfermai (Al-Hukkam: Journal of Islamic Family Law, 2022)
This article analyzes the determination of prospective marriage partners based on weton in Kandeman District, Batang Regency from the perspective of the 'urf. The type of research is field research with qualitative and descriptive characteristics by conducting interviews, observations, and documentation. The results of this study conclude that the reason the Kandeman District community still preserves the custom of calculating weton is as a servant's endeavor in his marriage to be happy, have abundant sustenance, and will not get a disaster. In the perspective of 'ufr calculations weton fall into two categories: ' urf amali sahih if it is done without any bad intentions, and 'urf amali fasid, if you carry out the tradition with total confidence with the results of the calculation or associate partners with Allah SWT